Analysing biographies in transnational educational spaces: Transitions to higher education of alumni from an IB school in Lisbon - Schippling, A.; Abrantes, P. (Globalisation, Societies and Education, 2024)
Taking the example of educational biographies of alumni of an IB World School in the Lisbon region, the article aims to explore the potential of the concept of transnational educational spaces for biographical research. We focus on the biographical stage of transition to higher education as a crucial phase of students’ biographies where we can observe constructions, reconfigurations and passages between (transnational) spaces. Our results show a bias to the British system at the transition to higher education, which also has implications for regarding the IB schools as transnational educational spaces.